Perspectives on tolerability and reasonableness. (1st June 2022) - Ban, N; Boyd, M; Coates, R; Cool, D A; Lecomte, J-F; Schneider, T
Abstract: Judgements on tolerability and reasonableness are central to the optimisation of protection. There are currently several international developments regarding these key considerations which will contribute to the review and evolution of the system of radiological protection. The IRPA15 International Congress brought together the principal issues currently under discussion, and the outcome of these discussions is presented.